A multistress responsive type I toxin-antitoxin system: bsrE/SR5 from the B. subtilis chromosome. Issue 5 (3rd May 2016) - Müller, Peter; Jahn, Natalie; Ring, Christiane; Maiwald, Caroline; Neubert, Robert; Meißner, Christin; Brantl, Sabine
ABSTRACT: bsrE /SR5 is a type I TA system from prophage-like element P6 of the B. subtilis chromosome. The 256 nt bsrE RNA encodes a 30 aa toxin. The antitoxin SR5 is a 163 nt antisense RNA. Both genes overlap at their 3′ ends. Overexpression of bsrE causes cell lysis on agar plates, which can be neutralized by sr5 overexpression, whereas deletion of the chromosomal sr5 copy has no effect. SR5 is short-lived with a half-life of ≈7 min, whereas bsrE RNA is stable with a half-life of >80 min. The sr5 promoter is 10-fold stronger than the bsrE promoter. SR5 interacts with the 3′ UTR of bsrE RNA, thereby promoting its degradation by recruiting RNase III. RNase J1 is the main RNase responsible for SR5 and bsrE RNA degradation, and PnpA processes an SR5 precursor to the mature RNA. Hfq stabilizes SR5, but is not required for its inhibitory function. While bsrE RNA is affected by temperature shock and alkaline stress, the amount of SR5 is significantly influenced by various stresses, among them pH, anoxia and iron limitation. Only the latter one is dependent on sigB . Both RNAs are extremely unstable upon ethanol stress due to rapid degradation by RNase Y.